KONDISI KEJIWAAN SAKIT BERUBAH AKAL PELAKU TINDAK PIDANA SEBAGAI ALASAN PENGHENTIAN PENYIDIKAN (Studi Kasus Di Polres Brebes) - Rokhmantono Rokhmantono (Jurnal Idea Hukum, 2018)
A criminal act committed by someone with a Psychiatric background Pain Turnedto reason is a crime that requires a special resolution by law enforcers, the investigator as a gateway entry of report of a criminal offence, has the task and authority for making arrests, investigations, inquiries and proceedings against such criminal acts. The research is the study of normative, analytical approach. This examination specification is a descriptive research. Research done in the area of law Polres Brebes, Central Java. The source of the legal materials used in the study of legal materials, namely primary, secondary and tertiary. Method of data collection with the study of librarianship. The presentation of the material law with descriptive narrative method. Methods of data analysis with qualitative, descriptive methods. Methods of data analysis with qualitative, descriptive methods. The results showed that psychiatric conditions ill change sense offender crime as the reason for termination of investigation can be accepted as the reason for termination of investigation cases, because the perpetrators of the crime have a history of less than perfect reasonable or crazy with these types of psychiatric disorders (Schizophrenia). Legal consequences of termination of the investigation of things criminal perpetrator by reason of psychological pain changed sense by investigators Polres Brebes is the offender referred to the Magelang mental hospital to undergo treatment and deeds from the process punishment, while all the goods seized are returned on a more right owners